Back Cover: Selective Imaging of the Angiogenic Relevant Integrins α5β1 and αvβ3 (Angew. Chem. Int. Ed. 44/2013). Issue 44 (2nd October 2013) - Neubauer, Stefanie; Rechenmacher, Florian; Beer, Ambros J.; Curnis, Flavio; Pohle, Karolin; D'Alessandria, Calogero; Wester, Hans‐Jürgen; Reuning, Ute; Corti, Angelo; Schwaiger, Markus; Kessler, Horst
<x xml:space="preserve">Abstract</x> In vivo tumor imaging by positron emission tomography (PET) is possible following the functionalization of α5β1 or αvβ3 subtype‐selective integrin antagonists with NODAGA. H. Kessler and co‐workers also show in their Communication on page 11656 ff. that these peptidomimetics are able to block bFGF‐ and VEGF‐stimulated angiogenesis in a rat aortic ring (RAR) assay, and exert anti‐tumor effects in a fibrosarcoma model in mice. (Picture designed by Philipp Ganthaler.)<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>